Increased Serum KL-6/MUC1 Level, Neutrophils and Lymphocytes Sputum in Malang Splendid Bird Market Workers - Zam Zam Firmansyah; Tri Wahju Astuti; Garinda Alma Duta (Jurnal Respirologi Indonesia, 2020)
Backgrounds: People who work in the bird market have a high exposure risk of air pollution in large numbers, particulate pollutans including organic dust, loose feathers, insects or ticks, food aerosol particles, bird’s excreta (amonia) and various of gram bacteria, fungal and virus. Exposure to particles will stimulate the immune system against harmful pathogens in the form of an inflammatory response. An infection or injury will stimulate secretion of KL-6/MUC1 (Krebs von den Lungen-6 is a high molecular weight, mucin-like glycoprotein in human (MUC1)) by AEC type II and bronchial epithelial cells in response to cell damage and regeneration. Methods: This was an observational analytic cross-sectional study on 35 subjects, which examined and analyzed the characteristics of workers, percentage count of neutrophils, lymphocytes in induced sputum and KL-6/MUC1 serum levels using ELISA sandwich. Results: Mean KL-6/MUC1 serum levels in the bird market workers increased (1152.67+583.92 U/ml) from normal levels (105.3-401.2 U/ml). There was a significant positive correlation between the length of exposure and KL-6/MUC1 serum levels (r=0.624; P